Food in Zones of Conflict: Cross-Disciplinary Perspectives - Paul Collinson, Helen Macbeth (Berghahn Books, 2014)
The editors of this book have long believed that the topic Food in Zones of Conflict should be the subject of a cross-disciplinary volume. While researchers, practitioners and writers of international reports tend to concern themselves with the literature and reports of their own academic discipline or professional field, we argue that studying the interaction between food and conflict necessarily involves consideration of factors which are of interest to a number of different specialists. Our ambition is that those interested in the food and nutritional security of those living in zones of conflict would gain a more holistic comprehension of the issues if they were able to read other perspectives encapsulated in one volume. We are fully aware that our selection of contributors and their subjects of enquiry cannot provide even a fraction of what a complete coverage of this very broad topic would involve. However, we feel that this juxtaposition of a wide range of perspectives demonstrates linkages and provides readers with an introduction to the different angles from which to view the topic. As we expect the book to be of general interest, every effort has been made to ensure that the material in all the chapters is accessible to a broad range of readers. Specialist language has been avoided. The editors had been able to discuss the issues with experts in different fields of study during two separate meetings. Our thanks, therefore, go to Oxford Brookes University and the International Commission on the Anthropology of Food and Nutrition [ICAF(UK)] for their support of one meeting, and to the Modern East Asian Research Centre (MEARC) at Leiden University for hosting and supporting an international conference, and to all those personnel who helped at both. We wish to acknowledge gratefully a grant from the Wenner Gren Foundation (Grant Number CONF-563), grants from the Netherlands Organisation for Scientific Research (NWO, VIDI Grant Number 276–53–003) and the Japan Foundation (Grant Number 23 RIE-RC- E11035). We thank Kat Mason warmly for help with checking references and assistance with compiling the Index of this volume.